Comparison of blocking strategies informed by precursor assessment to decrease pica. (18th February 2019) - Rettig, Lisa A.; Fritz, Jennifer N.; Campbell, Kelsey E.; Williams, Sarah D.; Smith, Leah D.; Dawson, Kyle W.
Abstract : Pica is dangerous behavior and often maintained by automatic reinforcement. We conducted a latency functional analysis (FA) using safe consumption items to verify that pica was maintained in part by automatic reinforcement and exclude participants for whom pica was likely maintained solely by attention. Next, we identified precursors to pica through a probability analysis and conducted a brief blocking assessment for participants' whose pica occurred in the alone and attention conditions of the FA. Finally, we compared blocking precursors with pica, touching an inedible item and the pica itself. Results showed that five of the six participants' pica was likely maintained by automatic reinforcement, and pica decreased during the brief blocking assessment for three of four participants. Results of the blocking comparison showed that blocking behaviors earlier in the response hierarchy was as effective as only blocking pica attempts for two participants and more effective for one participant.